Ranging behaviours across ecological and anthropogenic disturbance gradients: a pan-African perspective of giraffe (Giraffa spp.) space use - Brown, Michael Butler; Fennessy, Julian T; Crego, Ramiro D; Fleming, Christen H; Alves, Joel; Brandlová, Karolina; Fennessy, Stephanie; Ferguson, Sara; Hauptfleisch, Morgan; Hejcmanova, Pavla; Hoffman, Rigardt; Leimgruber, Peter; et al. (Proceedings. Biological sciences, 2023)
Animal movement behaviours are shaped by diverse factors, including resource availability and human impacts on the landscape. We generated home range estimates and daily movement rate estimates for 149 giraffe (Giraffa spp.) from all four species across Africa to evaluate the effects of environmental productivity and anthropogenic disturbance on space use. Using the continuous time movement modelling framework and a novel application of mixed effects meta-regression, we summarized overall giraffe space use and tested for the effects of resource availability and human impact on 95% autocorrelated kernel density estimate (AKDE) size and daily movement. The mean 95% AKDE was 359.9 km2 and the mean daily movement was 14.2 km, both with marginally significant differences across species. We found significant negative effects of resource availability, and significant positive effects of resource heterogeneity and protected area overlap on 95% AKDE size. There were significant negative effects of overall anthropogenic disturbance and positive effects of the heterogeneity of anthropogenic disturbance on daily movements and 95% AKDE size. Our results provide unique insights into the interactive effects of resource availability and anthropogenic development on the movements of a large-bodied browser and highlight the potential impacts of rapidly changing landscapes on animal space-use patterns.
Keywords: Afrika; productivity gradients; ekosystém; daily movement; pohyb; movements; home range; žirafy; antropogenní vlivy; Anthropogenic Effects; Africa; continuous time movement modelling; zvířata; Humans; Movement; Giraffes; Ecosystem; mixed effects meta-regression; lidé; Animals